The Role of Micro, Small, and Medium Enterprises (MSMEs) in Poverty Alleviation in Indonesia: A Systematic Literature Review - wahyudi, Wahyudi; Herman, Herman (The Kalimantan Social Studies Journal, 2026)
Micro, Small, and Medium Enterprises (MSMEs) occupy a strategic position in national economic development, particularly in efforts to reduce poverty and improve societal welfare. However, the realization of this role is not determined solely by economic factors, but is also strongly influenced by institutional quality and public governance practices. This study aims to systematically examine the contribution of MSMEs to poverty alleviation in Indonesia, while also identifying the major thematic clusters discussed in the literature. The research employs a Systematic Literature Review (SLR) method using a bibliometric approach based on RIS data. The findings indicate that MSMEs make a significant contribution to poverty reduction through job creation, income generation, strengthening local economic communities, and community empowerment, particularly in rural areas. The reviewed literature categorizes the role of MSMEs into several key clusters, including institutional and public policy aspects, improvement of poor households’ welfare, community-based local economic development, and the linkage between MSMEs and the Sustainable Development Goals (SDGs). Nevertheless, the effectiveness of MSMEs’ contributions is often constrained by weak governance, low levels of financial literacy, and corrupt political practices, which result in inequities in the distribution of policy benefits)